Influence of fibre type on the shear behaviour of engineered cementitious composite beams. Issue 9 (8th May 2021) - Ismail, Mohamed K.; Hassan, Assem A. A.
Abstract : The shear behaviour of large-scale engineered cementitious composite (ECC) beams reinforced with different types of fibre was evaluated. Four types of fibre were used: 8 and 12 mm long polyvinyl alcohol fibres (PVA8 and PVA12), 19 mm long polypropylene fibres (PP19) and 13 mm long steel fibres (SF13). An additional normal concrete (NC) beam of comparable compressive strength was cast and tested for comparison. The performance of all the test beams was evaluated through their load–deflection curves, cracking behaviour, first crack load, diagonal crack load, ultimate load, ductility and energy absorption capacity. The ultimate capacity and cracking moment of all the test beams were also compared with theoretical values estimated by some design code equations. The results indicated that, compared with the NC beam, all the ECC beams showed better performance in terms of cracking behaviour, shear capacity, ductility and energy absorption. The ECC beam reinforced with PVA8 fibres showed the highest shear strength and ductility of all the ECC beams with other polymeric fibres. Longer PVA fibres appeared to be less efficient than shorter ones. The beam reinforced with PP19 showed the lowest performance, while the use of SF13 proved to be the most effective in improving the first crack load, ultimate load, ductility and energy absorption capacity.